Diagnosing acute lacunar infarction using CT perfusion. (July 2016) - Cao, Wenjie; Yassi, Nawaf; Sharma, Gagan; Yan, Bernard; Desmond, Patricia M.; Davis, Stephen M.; Campbell, Bruce C.V.
Highlights: CT perfusion (CTP) identifies large vessel ischemic stroke with high sensitivity. We examined sensitivity for lacunar infarction (single perforating vessel occlusion). CTP abnormalities were identified in 56% of lacunar stroke patients. Mean transit time (MTT) was the most sensitive map type. Recognition of CTP abnormalities in lacunar stroke may improve diagnostic confidence. Abstract: The value of CT perfusion (CTP) in detecting acute lacunar infarcts (LACI) has not been well established. We tested the sensitivity of CTP for LACI. CTP maps of consecutive stroke patients from 2009–2013 were examined. MRI diffusion imaging was used to identify those with LACI. Two stroke neurologists independently evaluated the CTP maps for evidence of a perfusion lesion in a deep perforating artery territory. Cerebral blood volume (CBV), cerebral blood flow (CBF), mean transit time (MTT) and time to maximum (Tmax) maps were first examined in isolation and then in combination. Inter-observer agreement was measured using Cohen's κ. The lesions identified were later confirmed against the diffusion MRI reference and the sensitivity and specificity of CTP maps calculated. A total of 63 patient scans were analysed. There were 32 patients with MRI-confirmed LACI within the coverage of CTP; 18 in the striatum, 10 thalamic, and four in the corona radiata. Another 31 patients had normal MRI. Inter-rater agreement was good (κ = 0.83). Sensitivity (blinded consensus) was highest for MTT (56.2%) compared to Tmax (25%, p < 0.001), CBV (9.3%, p = 0.021) and CBF (43.7%, p < 0.001). MTT maps enable detection of a significant proportion of LACI using CTP.